دور الحوكمة المحلية في تحقيق التنمية الريفية المستدامة - معزوز, زكية (جامعة الوادي - University of Eloued, 2020)
في ظل مختلف المشاكل والاختلالات التنموية التي تعاني منها المناطق الريفية أو ما أطلق عليها بمصطلح مناطق الظل على مستوى البلاد، وأمام حتمية التنويع الاقتصادي وضرورة تحقيق التوازن الجهوي للتنمية، كان لابد من تكاثف مختلف الجهود من أجل ايجاد الحلول الناجعة للنهوض بواقع التنمية بهذه المناطق، خاصة وأننا نلاحظ مساهمتها المحورية في اقتصاديات عديد الدول التي حققت أشواطا متقدمة من التنمية المستدامة في عديد المجالات. ولعل أن أبرز هذه الحلول اليوم ونحن نشهد انطلاقة جديدة للدولة في جميع الميادين هو ما يعرف بالحوكمة المحلية، التي من شأنها تشكيل القاعدة السليمة، وتهيئة البيئة المثالية، وتوفير الشروط التكيفية مع خصوصيات هذه المناطق، والتي من شأنها دفع عجلة التنمية المستدامة بها. In light of the various development problems and imbalances that rural areas suffer from, or what has been called the term shadow areas at the country level, and in the face of the inevitability of economic diversification and the need to achieve regional balance for development, various efforts had to be intensified in order to find effective solutions to advance the realities of development in these areas, especially We note its pivotal contribution to the economies of many countries that have achieved advanced steps of sustainable development in many areas. Perhaps the most prominent of these solutions today, while we are witnessing a new start for the state in all fields, is what is known as local governance, which would form the right base, create an ideal environment, and provide adaptive conditions with the peculiarities of these areas, which would advance sustainable development in them.
The role of local governance in achieving sustainable rural development
مقال
Keywords: الحوكمة، الحوكمة المحلية، التنمية، التنمية الريفية، التنمية الريفية المستدامة.